Analysis of Take-Over Implementation in Risk Mitigation in Murabahah Griya Financing Products at Bank Syariah Indonesia KCP Mojosari - Lu’lu’il Maknuun; Kartika Andini (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
Due to the high-interest rates charged by conventional banks, many of their customers are looking to switch to Islamic financial institutions such as Bank Syariah Indonesia (BSI), where they can take advantage of debt takeovers or takeover of Murabahah Griya financing products. This research aims to analyze the Take Over of Bank Syariah Indonesia KCP Mojosari in Mitigating the Risk of Griya Murabahah Financing Products. This research uses a qualitative descriptive approach, with data collected from descriptions provided by researchers about phenomena in the field. Researchers conducted interviews and screened records to obtain information for this study. Based on the findings of this research, it can be concluded that the takeover of murabahah griya financing by Bank Syariah Indonesia is legal according to the provisions of DSN-MUI fatwa No.31/DSN-MUI/VI/2002. Bank Syariah Indonesia collects all documentation related to the takeover of financing, checks customer track records, and carries out financing restructuring in an effort to reduce risks related to the takeover of murabahah griya financing.